A Study Fable in Pair Work on ELT Learners' English Vocabulary Achievement: A Study Fable in Pair Work on ELT - Razaq, Yusuf; Satriani; Amiruddin; Bahri, Syamsul; Hasbi, Muhammad (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The purpose of this study was to determine whether teaching students fables in pairs of students during their second year of MA Nurul As'adiyah Callacu improved their vocabulary achievement. A pre-experimental methodology was used in this study's research in order to meet its goal. The academic year 2020–2021 was when the population was in its second year under MA Nurul As'adiyah Callacu. Purposive sampling was employed to obtain the sample. There were 17 students in the class that was selected from the X-A class with the most samples. According to the data analysis's findings, students' post-test mean scores (52.52) were higher than their pretest mean scores (32.23), and (52.52 – 32.23) was the gain score (20.29). The researcher used t-test statistical analysis for paired samples. The analysis of the data revealed that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted since the significance of the t value (0.000) was larger than the level of significance (0.05) and the degree of freedom (df) = 16. It can be inferred that using a fable in pair work can help students learn more vocabulary.